Development and characterization of 27 microsatellite markers for the mangrove fern, Acrostichum aureum (Pteridaceae) - Takashi Yamamoto; Yoshiaki Tsuda; Gustavo Maruyama Mori; Mariana Vargas Cruz; Yoshimi Shinmura; Alison K. S. Wee; Koji Takayama; Takeshi Asakawa; Takeru Yamakawa; Monica Suleiman; Juan Núñez-Farfán; Edward L. Webb; et al. (Botanical Society of America, 2016)
Premise of the study: Twenty-seven nuclear microsatellite markers were developed for the mangrove fern,Acrostichum aureum (Pteridaceae), to investigate the genetic structure and demographic history of the only pantropical mangrove plant.